The influence of chemical chaperones on enzymatic activity under thermal and chemical stresses: common features and variation among diverse chemical families. - Michal Levy-Sakin; Or Berger; Nir Feibish; Noa Sharon; Lee Schnaider; Guy Shmul; Yaniv Amir; Ludmila Buzhansky; Ehud Gazit (PLoS ONE, 2014)
Molecular and chemical chaperones are key components of the two main mechanisms that ensure structural stability and activity under environmental stresses. Yet, chemical chaperones are often regarded only as osmolytes and their role beyond osmotic regulation is not fully understood. Here, we systematically studied a large group of chemical chaperones, representatives of diverse chemical families, for their protective influence under either thermal or chemical stresses. Consistent with previous studies, we observed that in spite of the structural similarity between sugars and sugar alcohols, they have an apparent difference in their protective potential. Our results support the notion that the protective activity is mediated by the solvent and the presence of water is essential. In the current work we revealed that i) polyols and sugars have a completely different profile of protective activity toward trifluoroethanol and thermal stress; ii) minor changes in solvent composition that do not affect enzyme activity, yet have a great effect on the ability of osmolytes to act as protectants and iii) increasing the number of active groups of carbohydrates makes them better protectants while increasing the number of active groups of methylamines does not, as revealed by attempts to synthesize de novo designed methylamines with multiple functional groups.